2010
DOI: 10.1021/jp105428b
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Density Functional Methods for the Calculation of Small Gold Clusters

Abstract: The performance of various density functional theory methods on the geometries and energetics of Au(2), Au(3), Au(4), and Au(5) has been systematically evaluated. The results were compared with those from experiments or high-level wave function theory methods. In the present study, spin-orbit (SO) coupling was considered. It was found that SO coupling plays a very important role in the calculation of both the atomization energies and relative stability of the isomers of gold clusters. Functionals including SO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 148 publications
5
44
0
Order By: Relevance
“…26 Validation of DFT for the calculation of gold cluster has been studied by Li et al 27 and DFT methods have been used successfully to optimize the structures and assign all vibrational bands and predict frequencies and energies of molecule-metal complexes. 28 The calculations were carried out using the GAUSSIAN 09 software package.…”
Section: Methodsmentioning
confidence: 99%
“…26 Validation of DFT for the calculation of gold cluster has been studied by Li et al 27 and DFT methods have been used successfully to optimize the structures and assign all vibrational bands and predict frequencies and energies of molecule-metal complexes. 28 The calculations were carried out using the GAUSSIAN 09 software package.…”
Section: Methodsmentioning
confidence: 99%
“…Shi et al [238] studied neutral Au n clusters with n = 2-5 with 40 DFAs and found the best results with TPSSh [25] and M06-L.…”
Section: Geophysics Gold Clusters Metal-p Interactions and Layeredmentioning
confidence: 99%
“…Inertness and many of its unusual properties such that yellow color, nobility, and trivalency derive from relativistic effects [7]. Spin-orbit coupling has a significant effect on the cohesive energy and the relative stability of the isomers of gold clusters [8]. Its electronegativity is a result of the relativistic contraction of the valence 6s and 6p orbitals.…”
Section: Introductionmentioning
confidence: 99%